2012
DOI: 10.1111/j.2042-3292.2011.00368.x
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma in horses: Current perspectives

Abstract: SummaryDebate surrounding the nature of equine melanoma has resulted in an underestimation of its life-threatening potential. Contrary to popular dogma, the variable, often slow, rate of growth commonly associated with equine melanoma does not warrant benign classification. Equine melanoma is a malignant neoplasm with the capacity for local invasion and metastasis. A classification scheme was proposed in 1995, but this does not address the progressive nature of equine malignant melanoma (EMM). Additionally, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(96 citation statements)
references
References 35 publications
4
91
0
1
Order By: Relevance
“…26 Despite the benign phenotype of many melanocytic proliferations, most equine melanocytic neoplasms, other than melanocytic nevus, should be considered at least potentially malignant. 9 Variants of melanocytic nevi similar to those in humans have been reported in horses. 20 Although the diagnosis of melanocytic neoplasms in horses is typically straightforward due to heavy pigmentation, equine melanomas may be amelanotic or poorly pigmented.…”
mentioning
confidence: 65%
“…26 Despite the benign phenotype of many melanocytic proliferations, most equine melanocytic neoplasms, other than melanocytic nevus, should be considered at least potentially malignant. 9 Variants of melanocytic nevi similar to those in humans have been reported in horses. 20 Although the diagnosis of melanocytic neoplasms in horses is typically straightforward due to heavy pigmentation, equine melanomas may be amelanotic or poorly pigmented.…”
mentioning
confidence: 65%
“…In-transit lesions, on the other hand, are tumors found at a greater distance to the primary melanoma, but still within the drainage area of the same lymph node draining the primary tumor (Hasney et al 2008). Moore et al (2013) proposed a clinical classification into 4 progressing stages in which horses showing only a single melanoma with a diameter < 2 cm and a slow growth is classified as stage 1. Stage 2 describes horses with multiple small (< 2 cm) tumours without dissemination or metastases and a slow or quiescent growth pattern.…”
Section: Nature Of Emmmentioning
confidence: 99%
“…Despite their initially slow invasive growth, they frequently metastasize later (Baker and Leyland 1975, Valentine 1995, Fleury et al 2000a, Smith et al 2002. For further information on clinical signs and conventional therapeutic options, the reader is referred to recent extensive reviews on the matter (Metcalfe et al 2013, Moore et al 2013, Phillips and Lembkke 2013, Cavalleri et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Although some authors, predominantly in earlier research articles, suggested a non-neoplastic aetiology of the disease (Rodriguez et al 1997, Sutton andColeman 1997), EMM is now generally accepted as a neoplastic condition (Gorham and Robl 1986, Macgillivray et al 2002, Patterson-Kane and Ginn 2003, Seltenhammer et al 2004, Moore et al 2013). Due to the high incidence of malignancy in equine melanomas Moore and colleagues (2013) proposed to use the term equine malignant melanoma when referring to equine melanomas because of their general malignant potential (Moore et al 2013). Since most melanomas undergo a transformation from benign to malignant, within this review article the authors follow their recommendation and use the term EMM.…”
Section: Aetiological Basis Of Emmmentioning
confidence: 99%
“…The disease was recently reviewed (Metcalfe et al 2013, Moore et al 2013, Phillips and Lembcke 2013 and the term equine malignant melanoma (EMM) was proposed by Moore and colleagues (2013) to describe the common melanocytic disease occurring in horses, considering the malignant potential of this tumour during its course of disease. This review describes the aetiological basis of EMM, the genetic influence in its development, diagnosis, and the current therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%